Stroke as a civilization disease - Agata Trzebiatowska; Jakub Husejko; Daria Bieniek; Natalia Skierkowska; Beniamin Szmelcer; Michał Wilczyński; Monika Prylińska; Patrycja Wszelaki; Kornelia Kędziora- Kornatowska (Kazimierz Wielki University, 2018)
Background: Stroke is one of the three leading causes of death in the world. Young people are also more and more affected. The reasons for this phenomenon are divided into two categories, modifiable and non-modifiable. The former include: hypertension, dyslipidemia, diabetes or cardiovascular disease. Factors that can not be modified include age, gender, race, as well as genetic predispositions and previous impacts. Behind the main principles of primary prevention means: regular monitoring of blood pressure, treatment of metabolic disorders, carotid angioplasty, and most important lifestyle change. The secondary principles of prophylaxis include antiplatelet therapy, anticoagulant therapy as well as surgical treatment. The aim of the study was to present stroke as a disease of civilization, with particular regard to its possible pathogenesis and prevention. Materials and methods: The literature was reviewed from the medical databases PubMed, Google Scholar and EBSCO. We adopted as key words: stroke, prevention, cerebral infarction, civilization disease. Results: Stroke has become a civilization disease. It is more and more often the cause of deaths in Poland and in the world. Epidemiology of this phenomenon has been thoroughly known. Risk factors for the incidence of stroke have been grouped, as well as methods for preventing and treating this phenomenon. Conclusions: The stroke affects more and more people. Its causes have been known. These include risk factors that can be modified by, for example, changing lifestyle.